2019
DOI: 10.1002/adfm.201901895
|View full text |Cite
|
Sign up to set email alerts
|

One Stimulus In Situ Induces Two Sequential Luminescence Switchings in the Same Solvent‐Fuming Process: Anthracene Excimer as the Intermediate

Abstract: Commonly, one stimulus only induces one luminescence switching in stimuli-responsive experiment. Herein, it is reported that one stimulus in situ induces two luminescent switches, resulting from two phase transitions in a solvent-fuming process. Two phase transitions are in situ composed of a first fast and a subsequent slow process, corresponding to the change of molecular packing from the amorphous state to the π-π dimer crystalline state to the cocrystalline state with the inclusion of solvents, accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…The development of stimuli-responsive organic fluorescent materials has received tremendous attention as a result of their fundamental research and promising applications in information storage, 1,2 anti-counterfeiting paper, 3,4 sensors [5][6][7] and bioimaging. [8][9][10] In particular, mechanochromic (MC) materials that use mechanical force as a stimulus have been recognized as ideal candidates for preparing anti-counterfeiting labels and pressure-sensitive devices.…”
Section: Introductionmentioning
confidence: 99%
“…The development of stimuli-responsive organic fluorescent materials has received tremendous attention as a result of their fundamental research and promising applications in information storage, 1,2 anti-counterfeiting paper, 3,4 sensors [5][6][7] and bioimaging. [8][9][10] In particular, mechanochromic (MC) materials that use mechanical force as a stimulus have been recognized as ideal candidates for preparing anti-counterfeiting labels and pressure-sensitive devices.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the aggregates, especially the excimer and exciplex, that are used are believed to be of low-efficiencies, recently, our group have reported a series of highly efficient excimer fluorescent materials. [9][10][11] For example, with systematically regulated side-group substitutions, the optimized structure 2-(anthracen-9-yl) thianthrene (2-TA-AN) exhibits a green excimer emission at 526 nm with a considerably high PLQY of 80% compared with its deep-blue, but low-efficiency monomer emission (424 nm, PLQY = 33%). 12 However, the present excimer is that the molecular structure of these efficient excimers is limited to anthracene derivatives, which can only produce a green emission.…”
Section: Introductionmentioning
confidence: 99%
“…30 With further studies of the AIE effect, a large number of AIE molecules have been found to exhibit stimulus-responsive fluorescence switching characteristics, which greatly promotes the development of organic solid-state fluorescent materials. 26,[31][32][33][34][35][36] Nevertheless, most of the reported examples display a reversible two-color luminescence switching, and multicolor switching materials remain extremely scarce due to the un-designability of these kinds of smart materials. Moreover, the successful cases that can clearly illuminate the luminescence switching mechanisms are very few because the metastable state is hard to control and obtain, resulting in the absence of structural evidence (X-ray crystal structures).…”
Section: Introductionmentioning
confidence: 99%